Characteristics of Hospitals Diverting Ambulances in a California EMS System. Issue 1 (22nd January 2014) - Kahn, Christopher A.; Stratton, Samuel J.; Anderson, Craig L.
Abstract: Introduction: While several reports discuss controversies regarding ambulance diversion from acute care hospitals and the mortality, financial, and resource effects, there is scant literature related to the effect of hospital characteristics. Hypothesis/Problem: The objective of this study was to describe specific paramedic receiving center characteristics that are associated with ambulance diversion rates in an Emergency Medical Services system. Methods: A retrospective observational study design was used. The study was performed in a suburban EMS system with 27 paramedic receiving centers studied; one additional hospital present at the beginning of the study period (2000-2008) was excluded due to lack of recent data. Hospital-level and population-level characteristics were gathered, including diversion rate (hours on diversion/total hours open), for-profit status, number of specialty services (including trauma, burn, cardiovascular surgery, renal transplant services, cardiac catheterization capability [both interventional and diagnostic], and burn surgery), average inpatient bed occupancy rate (total patient days/licensed bed days), annual emergency department (ED) volume (patients per year), ED admission rate (percent of ED patients admitted), and percent of patients leaving without being seen. Demographic characteristics included percent of persons in each hospital's immediate census tract below the 100% and 200% poverty lines (each considered separately), and population density within the census tract. Bivariate and regression analyses were performed. Results: Diversion rates for the 27 centers ranged from 0.3%-14.5% (median 4.5%). Average inpatient bed occupancy rate and presence of specialty services were correlated with an increase in diversion rate; occupancy rate showed a 0.08% increase in diversion hours per 1% increase in occupancy rate (95% CI, 0.01%-0.16%), and hospitals with specialty services had, on average, a 4.1% higher diversion rate than other hospitals (95% CI, 1.6%-6.7%). Other characteristics did not show a statistically significant effect. When a regression was performed, only the presence of specialty services was related to the ambulance diversion rate. Conclusions: Hospitals in this study providing specialty services were more likely to have higher diversion rates. This may result in increased difficulty getting patients requiring specialty care to centers able to provide the needed level of service. Major limitations include the retrospective nature of the study, as well as reliance on multiple data systems. C Kahn, S Stratton, C Anderson .Characteristics of hospitals diverting ambulances in a California EMS system .Prehosp Disaster Med .2014 ;29 (1 ):1 -5 .